Chloroquine Urea Derivatives: Synthesis and Antitumor Activity in Vitro - Pavić Kristina; Rajić Zrinka; Mlinarić Zvonimir; Uzelac Lidija; Kralj Marijeta; Zorc Branka (Acta Pharmaceutica)
In the current paper, we describe the design, synthesis and antiproliferative screening of novel chloroquine derivatives with a quinoline core linked to a hydroxy or halogen amine through a flexible aminobutyl chain and urea spacer. Synthetic pathway leading to chloroquine urea derivatives 4-10 includes two crucial steps: i) synthesis of chloroquine benzotriazolide 3 and ii) formation of urea derivatives through the reaction of compound 3 with the corresponding amine. Testing of antiproliferative activity against four human cancer cell lines revealed that chloroquine urea derivatives 9 and 10 with aromatic moieties show activity at micromolar concentrations. Therefore, these molecules represent interesting lead compounds that might provide an insight into the design of new anticancer agents.